The Influence of ZIS Fund Distribution, Sharia Financing, and Social assistance program Program on Poverty Alleviation: The Mediating effect of Islamic Human Development Index - Awaliah, Siti Farika Nurul; Badina, Tenny; Pardiansyah, Elif (Universitas Siliwangi, 2024)
Introduction to The Problem: The poverty level in Indonesia will increase at the end of 2022, while the growth in the realization of distribution of ZIS funds, Sharia Financing, Social assistance program Program and I-HDI, represented by IPM, will experience good growth and increase significantly in 2022.Purpose/Objective Study: This research aims to determine (1) the influence of distribution of ZIS funds on poverty, (2) sharia financing on poverty, (3) social assistance program funds on poverty, and (3) Islamic human development index as a mediator between the influence of ZIS, sharia financing, and social assistance program for poverty alleviation.Design/Methodology/Approach:The method used in this research is descriptive quantitative, with a sample of 10 provinces with the largest Muslim population in Indonesia. The data used is secondary data obtained from the official website of the relevant institution. Data were processed using Smart PLS 4.0.9 software and analyzed using the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) approach.Findings: The results of this research show that (1) the distribution of ZIS funds has a significant negative effect on poverty, (2) sharia financing has a significant negative effect on poverty, (3) social assistance program has a significant positive effect on poverty, (4) the Islamic human development index is able to mediate the effect of distribution ZIS funds, sharia financing, and social assistance program towards poverty alleviation.Paper Type: Research Article